The Economics of an Import Tariff in the Keynesian Model: An Intermediate Macroeconomics Treatment - Vasilev, Aleksandar (Theoretical and Practical Research in Economic Fields; Vol 16 No 4 (2025): TPREF Special Issue, Volume XVI, Issue 4(36), Winter 2025DO - 10.14505/tpref.v16.4(36).03, 2025)
The standard textbook treatment of expansionary fiscal policy at intermediate macroeconomics level, e.g. , Blanchard (2024), Burda and Wyplosz (2023), only consider taxes affecting the economy through the consumption function, by increasing the level of disposable income. Motivated by recent events - the import tariffs introduced in the US by Trump administration - in this paper we introduce such tariffs to explore how they work in the Keynesian cross framework. As expected, an increase in import tariffs stimulates aggregate demand, which is the ”import substitution effect” from the trade literature. There is also a multiplier effect, which we refer to the ”import tariff multiplier effect.” This possible stimulus effect on the domestic (US) economy from an increase in the import tariff rate is of interest to policy-makers, and in developing countries with a public finance model organized around trade taxation, or countries that follow an export-led growth model by discouraging imports.